MPC-03 IMMUNOHISTOCHEMICAL ANALYSIS OF TUMOR ASSOCIATED MACROPHAGE INDUCED AFTER BIODEGRADABLE CARMUSTINE WAFER IMPLANTATION IN HUMAN GLIOBLASTOMA. (16th December 2019) - Shibahara, Ichiyo; Hagiwara, Hiroyuki; Miyasaka, Kazuhiro; Sato, Sumito; Inukai, Madoka; Yasui, Yoshie; Hide, Takuichiro; Kumabe, Toshihiro
Abstract: The carmustine (BCNU) wafer, a biodegradable polymer, currently is the only drug that is able to be placed at the surgical site to treat malignant tumors. Biomaterials to treat cancers hold therapeutic potential; however, how they behave inside the tumor microenvironment requires further study. We previously investigated the tumor microenvironment after BCNU wafer implantation, and found that CD68-positive macrophage was significantly introduced around the wafer (Shibahara et al. J Neurooncol 2018). Recent studies demonstrated the importance of tumor-associated macrophage (TAM). However, we could not clarify whether the increased macrophage around the wafer was pro-tumor or anti-tumor phenotype. In the present study, we immunohistochemically examined expressions of CD68, IBA1, CD163, TMEM119, BIN1, CD31, and VEGF to investigate TAM after the wafer implantation. Quantitative evaluation revealed that CD68-positive cells were significantly increased (P = 0.0009), whereas TMEM119-positive cells were significantly decreased (P = 0.0081) after wafer implantation compared to tissue from cases without wafer implantation. CD163, a known marker of poor prognosis in glioblastoma, did not differ with and without wafer implantation. Among factor analyzed, BCNU wafer did not induce protumor TAM, but reduced microglial marker, TMEM119. In addition to the aspect of chemotherapy, BCNU wafer may have potential to modify the tumor microenvironment such as TAM.